Selectivity Trends between Oxygen Evolution and Chlorine Evolution on Iridium-Based Double Perovskites in Acidic Media - Vos, Johannes G.; Liu, Zhichao; Speck, Florian; Perini, Nickson; Fu, Wentian; Cherevko, Serhiy; Koper, Marc T.M. (ACS Catalysis, 2019)
The electrochemical chlorine evolution reaction (CER) and oxygen evolution reaction (OER) represent core processes in the production of chlorine, relevant to bulk chemical manufacturing, and water splitting, the most promising technology for renewable energy storage. Unfortunately, because of an apparent coupling between their key binding intermediates, the two reactions can easily occur simultaneously, which is never an attractive outcome. In this work, using a series of iridium-based double perovskites and rotating ring-disk voltammetry to deconvolute parallel OER and CER currents, we explored the interdependence of CER and OER in dilute acidic chloride solutions of up to 120 mM, where both reactions may occur in parallel with similar current densities. We also employed online inductively coupled plasma-mass spectrometry (ICP-MS) measurements to probe the material stability and its dependence on chloride concentration. For all studied materials, we found a strong linear correlation between CER and OER activity as well as a comparable selectivity, strengthening the suggestion that OER and CER follow a scaling relationship. It was also found that chloride selectively enhances the dissolution of the noble metal component. A reaction order analysis was performed to gain insight into the CER mechanism, the effect of surface area changes due to adventitious leaching, and the observed suppressing effect of chloride on OER.
CRIS-Team Scopus Importer:2019-09-17
Keywords: chlorine evolution; electrocatalysis; electrochemical mass spectrometry; iridium dissolution; oxygen evolution; rotating ring-disk electrode; selectivity